2008
DOI: 10.1186/1447-056x-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Under-diagnosis of alcohol-related problems and depression in a family practice in Japan

Abstract: AimThe aim of this survey was to assess the accuracy of a family physician's diagnosis of depression and alcoholism.MethodsConsecutive new adult patients attending a family practice in Japan between April 2004 and August 2006 were enrolled. Excluded were those with dementia or visual disturbance, and emergency cases. Participants completed a questionnaire regarding their complaints and socio-demographics. A research nurse conducted the Japanese version of the Mini-International Neuropsychiatric Interview (J-MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…19 In a study in Japan, almost half of the cases of major depression were identified using the Mini-International Neuropsychiatric Interview (MINI) in a family practice in Japan (kappa 0.43), but all the cases of alcoholism were missed. 20 The referring doctors in the present survey had an insufficient level of diagnostic accuracy for psychiatric disorders. Some psychotropic medications might be prescribed inappropriately to elderly patients with delirium or depression as a result of the lack of an accurate psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…19 In a study in Japan, almost half of the cases of major depression were identified using the Mini-International Neuropsychiatric Interview (MINI) in a family practice in Japan (kappa 0.43), but all the cases of alcoholism were missed. 20 The referring doctors in the present survey had an insufficient level of diagnostic accuracy for psychiatric disorders. Some psychotropic medications might be prescribed inappropriately to elderly patients with delirium or depression as a result of the lack of an accurate psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 64%
“…When the Structured Clinical Interview for DSM‐III‐R (SCID) was used, the kappa statistics estimated among mental health professionals within the same hospital were 0.76 for alcohol‐related disorder, 0.42 for current major depression and 0.65 for panic disorder among non‐psychiatric patients 19 . In a study in Japan, almost half of the cases of major depression were identified using the Mini‐International Neuropsychiatric Interview (MINI) in a family practice in Japan (kappa 0.43), but all the cases of alcoholism were missed 20 …”
Section: Discussionmentioning
confidence: 99%
“…The J‐MINI was used to divide participants into two groups: MDE group (MDE is diagnosed if five or more of the nine items are present) and non‐MDE group (MDE is not diagnosed if less than five items are present). Major studies using the J‐MINI have been performed on psychiatric patients 38 and outpatients 39–41 …”
Section: Methodsmentioning
confidence: 99%
“…Major studies using the J-MINI have been performed on psychiatric patients 38 and outpatients. [39][40][41] Procedures Before we collected data in an institution, we received the approval from the person who is in charge of the institution. The researchers conducted the surveys after the informed consent was obtained from all participants.…”
Section: Japanese Version Of the Mini-international Neuropsychiatric mentioning
confidence: 99%
“…A meta-analysis of the validity and reliability of the PHQ-9 as a screening tool at various cutoff points concluded that at a cut-off of 10, the PHQ-9 has a pooled sensitivity of 0.78 and specificity of 0.87, which is adequate [14]. In primary care, the best cut-off for detecting depression using the PHQ-9 was estimated at 11, with a sensitivity of 0.76 and specificity of 0.81 [15]. Taking these into consideration, along with the DSM-5 criteria for diagnosis of depression where 5 out of 9 symptoms are required, we considered a cut-off of 9 in this study (taking a positive score of ≥2 on all questions other than question 9, where a score ≥1 was considered positive, thus making a total score of 8+1 as the cut-off).…”
Section: Study Toolsmentioning
confidence: 99%